Benzbromarone Stabilizes ΔF508 CFTR at the Cell Surface - Loo, Tip W. (American Chemical Society, 2011)
[Image: see text] Deletion of Phe508 from the first nucleotide-binding domain of the CFTR chloride channel causes cystic fibrosis because it inhibits protein folding. Indirect approaches such as incubation at low temperatures can partially rescue ΔF508 CFTR, but the protein is unstable at the cell surface. Here, we show that direct binding of benzbromarone to the transmembrane domains promoted maturation and stabilized ΔF508 CFTR because its half-life at the cell surface was ∼10-fold longer than that for low-temperature rescue. Therefore, a search for small molecules that can rescue and stabilize ΔF508 CFTR could lead to the development of an effective therapy for cystic fibrosis.